Profits and principles : Benhaven Learning Network - Oster, Sharon M.; Garstka, Stanley J.; Dong, Jennifer; Robinson, Heather ([London] : SAGE, 2016)
Larry Wood, the Executive Director of Benhaven, Inc., picked up his last annual financial report for the organization. During his recent meeting with the Board of Directors, the members had asked difficult questions about the disappointing year-end financial results of Benhaven's for-profit venture, Benhaven's Learning Network (BLN). While BLN had met its targets in its first year of operations, the current year had been more disappointing. Larry understood the Board's concern, but also believed that BLN needed to grow at its own pace. Linda Grimm currently ran BLN and served as both the Director and Managing Consultant of the venture. As Larry contemplated contacting Linda, he knew that she was usually very busy and probably would not share the Board's concern about growth. This case study examines this topic.
Originally Published in: Oster, S. M., Garstka, S., Dong, J., & Robinson, H. (2004). Profits and Principles: Benhaven Learning Network. 00-011. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Benhaven (School); Nonprofit organizations -- Management -- Case studies; Nonprofit organizations -- Finance -- Case studies